K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

Đặt \(B=2^{2013}+2^{2012}+...+2^2+2+1\)

\(\Leftrightarrow A=2^{2014}-B\)

Ta có: \(B=2^{2013}+2^{2012}+...+2^2+2+1\)

\(\Leftrightarrow2B=2^{2014}+2^{2013}+...+2^3+2^2+2\)

\(\Leftrightarrow B=2^{2014}-1\)

\(\Leftrightarrow A=2^{2014}-B=2^{2014}-2^{2014}+1=1\)

12 tháng 3 2019

\(\frac{\frac{1}{2012}+\frac{1}{2013}-\frac{1}{2014}}{\frac{5}{2012}+\frac{5}{2013}-\frac{5}{2014}}-\frac{\frac{2}{2013}+\frac{2}{2014}-\frac{2}{2015}}{\frac{3}{2013}+\frac{3}{2014}-\frac{3}{2015}}\)

=\(\frac{\frac{1}{2012}+\frac{1}{2013}-\frac{1}{2014}}{5\left(\frac{1}{2012}+\frac{1}{2013}-\frac{1}{2014}\right)}-\frac{2\left(\frac{1}{2013}+\frac{1}{2014}-\frac{1}{2015}\right)}{3\left(\frac{1}{2013}+\frac{1}{2014}-\frac{1}{2015}\right)}=\frac{1}{5}-\frac{2}{3}=\frac{3}{15}-\frac{10}{15}=-\frac{7}{15}\)

A=22014-22013-22012-...-22-2-1

2A=22015-22014-22012-...-23-22-2

2A-A=(22015-22014-22013-...-23-22-2)-(22014-22013-22012-...-22-2-1)

A=22015-1

28 tháng 11 2016

Mình không biết

29 tháng 11 2016

Theo suy đoán thì mình ra 1

\(A=2^{2014}-2^{2013}-2^{2012}-......-2^2-2-1\)

\(\Rightarrow\left(-2\right)\times A=-2^{2015}+2^{2014}+2^{2013}+.....+2^3+2^2+2\)

\(\Rightarrow-2A+A=-A=-2^{2015}-1=-\left(2^{2015}+1\right)\)

\(\Rightarrow A=2^{2015}+1\)